Dose-dependent effect of caffeine supplementation on judo-specific performance and training activity: a randomized placebo-controlled crossover trial - Durkalec-Michalski, K.; Nowaczyk, P. M.; Glówka, N.; Grygiel, A (Journal of the International Society of Sports Nutrition, 2019)
Background: Caffeine (CAF) supplementation could have a positive impact on physical performance and sport abilities. Nevertheless, the CAF-induced, dose-dependent influence on discipline-specific performance and combat activity in combat sports have not been sufficiently investigated. The aim of this study was to examine the effect of single ingestion of 3, 6, or 9 mg/kg body weight of CAF and placebo (PLA) on judo-specific performance and sparring combat activities. Methods: In a randomised double-blind placebo-controlled cross-over design, acute pre-exercise supplementation with CAF (3, 6, or 9 mg/kg body weight) and placebo PLA in 22 male highly-trained judoists was examined. The study protocol involved five separate testing sessions using the Special Judo Fitness Test (SJFT) with heart rate monitoring, three judo sparring combats and evaluation of the rate of perceived exertion (RPE) using the Borg scale. Results: Six and 9 mg/kg CAF improved SJFT performance, while 9 mg/kg increased combat activity. Three mg/kg CAF lacked any apparent positive ergogenic effect. Among athletes, who include CAF-containing products in their habitual diet (consumers), only 9 mg/kg CAF effectively enhanced SJFT performance, while in those who do not consume CAF-containing products at regular basis (non-consumers), the enhancing effect was achieved even at 6 mg/kg. Conclusions: Regarding combat sports, higher (6-9 mg/kg) than currently recommended CAF dosages (3-6 mg/kg) are apparently more effective in terms of judo-specific performance. However, the ergogenic CAF effect is not only dose-dependent, but it is also related to customary CAF consumption.